The Effect of Operating Cash Flow, Leverage, Profitability, and Liquidity on Corporate Income Tax in Consumer Non-Cyclical on the Indonesia Stock Exchange in 2021–2024 - Siti Fatimah; Ruslaini Ruslaini; Yessica Amelia (International Journal of Economics and Management Research, 2025)
This study examines whether operating cash flow, leverage, profitability, and liquidity affect corporate income tax in consumer non-cyclical companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2024 period. This research was conducted because corporate income tax payments in this sector tend to fluctuate and previous studies show inconsistent results. The purpose of this study is to identify which internal financial factors influence corporate income tax. This study uses a quantitative approach with secondary data obtained from audited annual financial statements. The population consists of 131 consumer non-cyclical companies, and 16 companies were selected as samples using purposive sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The results show that operating cash flow has a positive and significant effect on corporate income tax, meaning that companies with higher operational cash inflows tend to pay higher corporate income tax. Leverage has a significant negative effect, indicating that higher debt levels reduce taxable income through interest expenses. Meanwhile, profitability and liquidity do not have a significant effect on corporate income tax. Overall, this study shows that cash flow and capital structure are more relevant in explaining corporate income tax than profitability and liquidity in consumer non-cyclical companies.